Pengaruh Media Sosial terhadap Minat Berkunjung Kembali Wisatawan Lokal di Masa Pandemi ke Daya Tarik Wisata Khusus Kintamani Bali - Ni Putu Ratna Sari (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
Bali undoubtedly faces the most severe impacts from the COVID-19 pandemic. As the new normal era comes, the Balinese starts visiting some tourist destinations. Social media postings about tourists' visit enjoying Kintamani's panorama have attracted other tourists to travel on the weekend or on the vacation. This research objective were to find out the role of social media in promoting tourist attractions in Kintamani, Bangli regency, Bali; and to investigate impacts of social media to revisit Kintamani. This research utilized quantitative approach of multiple regression analyses. Result of this research showed that the social media were found to be effective in triggering interest of visitation during COVID-19 pandemic. In addition, easiness, trust, and information quality variables simultanously cause positive impacts and significantly (53.9%) impacts on interest to revisit Kintamani. This research contributed to the businessmen in utilizing social media to promote and sell their tourism products during the pandemic era.